Interactive multimedia book program in environmental science learning in fourth grade students of elementary school - Callao - Solís Toscano, José Luis (2021)
This research is about a study of the levels of learning in students of fourth grade of primary level of an educational institution, Callao, in which was used an interactive program as a tool to improve the learning of the biodiversity. This interactive program LIM consist of a set of multimedia educational activities like crosswords, puzzles, text exercises, questions, memory games, secret word activities and others. The sample was conformed by 30 boys and girls between 9 and 11 years old. The simple descriptive design was used. Test of Sevillano (1995) was applied like a measure instrument. It was adapted by Jose Luis Solis (2009). Results show that students who use the interactive program have a high level of learning about biodiversity. I conclude that the high achievement reached improves the learning of students.